(untitled) (Proceedings of the International Conference on Education, 2021)
The Suzuki Method defines musical abilities as not innate but one that can be developed. It is worth emphasizing that children with autism spectrum disorders could play an instrument from an early age by listening to music, imitating the game’s teacher, parent, friend, repeating and perfecting songs. Key question: what is the relationship between using the Suzuki Method and developing communication skills, social competencies, and cognitive skills of students on the autism spectrum? The goal is to design a proprietary model with students in the autism spectrum based on the Suzuki Method for remote work. For the main problem, the independent variable uses the Suzuki Method with autism spectrum students aged 7 to 11. The dependent variable results from the observational technique of student’s communication skills, social competencies, and cognitive skills. An individualization experiment has been undertaken in the case study procedure. These will be case reports during the action research. A child on the autism spectrum disorder has good visual memory, developed match skills, and has the perfect pitch. Presumably, the research goals and indicators are not overestimated during Suzuki’s remote lessons, too. Research can significantly accelerate reconstructive inclusion in a child.